Method and use of dual-ligand MOFs for preparing nitrogen-doped mesoporous carbon nanoalloy catalysts
By using the dual ligand MOFs material to prepare nitrogen-doped mesoporous carbon nanoalloy catalysts, the problems of low selectivity and decreased activity of existing catalysts when catalyzing the conversion of furfural to cyclopentanone are solved, and efficient and stable catalytic effects are achieved, which are suitable for industrial applications.
Patent Information
- Application Number
- CN202310150327.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-02-22
AI Technical Summary
During the process of catalyzing the conversion of furfural to cyclopentanone, existing catalysts have low selectivity and decreased activity after recycling, making it difficult to meet the needs of industrial production.
The biligand MOFs material tetra(4-methoxycarbonylphenyl)porphyrin and phenylenetriacetic acid were used as precursors to prepare a nitrogen-doped mesoporous carbon nanoalloy catalyst by heat treatment for catalytic conversion of furfural to cyclopentanone.
The catalyst has high selectivity and stability, can be recycled multiple times, meets the requirements of industrial production, and is environmentally friendly, safe and non-toxic.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and specifically relates to a method for preparing an alloy nanocatalyst loaded with nano-mesoporous carbon having hierarchical pores by using porphyrin-based MOFs, and application of the catalyst in synthesizing cyclopentanone compounds using furfural as a biomass-based raw material. Background Art
[0002] Using biomass to produce valuable chemicals is an effective way to reduce dependence on fossil resources and increase the supply of organic fine chemicals. Furfural (FFA), a furan aldehyde derived from lignocellulose, is an important bio-based platform compound and is positioned as a stable and renewable source of organic non-fossil carbon. It can be used to produce value-added chemicals and fuels. Furfural is a multifunctional compound (with a furan ring and a carbonyl group). Through various catalytic reduction, ring-opening and other reactions, a variety of fine chemicals can be prepared, such as the efficient synthesis of cyclopentanone (CPO) and cyclopentanol (CPL) through catalytic hydrogenation and isomerization reactions. Among them, cyclopentanone (CPO) is an important raw material for fine chemicals, used in the production of medicines, pesticides, dyes and fragrances.
[0003] In the process of furfural conversion to cyclopentanone, in order to improve the raw material conversion rate and product selectivity and reduce production costs, researchers have studied and developed various catalysts. "Biomass-derived furfural conversion over Ni / CNTcatalysts at the interface of water-oil emulsion droplets", HERRERA C et al. used liquid-liquid interface Ni nanoparticles and distributed them on the interface of emulsion droplets to form a stable Pickering emulsion, and then prepared the catalyst (referred to as Ni / CNTox) by carbon nanotube loading. Ni / CNTox is an effective catalyst for the conversion of furfural to cyclopentanone. Under the optimized conditions (using water as solvent, 200℃, 2MPa H2, 1h), the furfural conversion rate is 35% and the cyclopentanone yield is 25%. The catalyst has low selectivity for the conversion of furfural to cyclopentanone, and after three cycles, the CPO yield decreases significantly, making it difficult to continue to catalyze effectively and not suitable for industrial production applications.
[0004] "Pd / Cu-MOF as a highly efficient catalyst for synthesisofcyclopentanone compounds frombiomass-derived furanic aldehydes", DENG Q et al. used Cu-MOFs (such as Cu3(BTC)2) carriers with different chemical structures to prepare Pd / Cu-MOFs precursors, and then annealed them to obtain Pd / Cu-C bifunctional catalysts. Since Cu-BTC (metal ions are bridged by trimer acid) has strong acidity, it can effectively fix Cu and Pd metal ions and make them dispersed evenly and orderly. In the catalytic reaction of furfural to cyclopentanone, the catalyst activity decreased after 5 cycles. TEM analysis showed that compared with the high dispersion of Pd nanoparticles on the catalyst before the reaction, the Pd nanoparticles on the catalyst after 5 cycles were severely aggregated. The N2 adsorption-desorption process after the catalyst was cycled 5 times also showed that the specific surface area of the catalyst decreased significantly, which was the reason for the decrease in catalyst activity.
[0005] Therefore, it is of great significance to prepare a catalyst with good selectivity and high stability that promotes the conversion of furfural into cyclopentanone and realize its industrial application. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing a nitrogen-doped mesoporous carbon nanoalloy catalyst using dual-ligand MOFs. The preparation method uses tetrakis(4-methoxycarbonylphenyl)porphyrin (T(4-COOCH3)PP) and trimesic acid (BTC) as dual-ligand MOFs materials (referred to as M-TCOPP-BTC-MOF) as precursors to prepare a nitrogen-doped mesoporous carbon-loaded transition metal alloy nanocatalyst. The catalyst can be used to catalyze the conversion of furfural into cyclopentanone, has the characteristics of good selectivity and high stability, and can be applied in industry.
[0007] To achieve the above object, the present invention adopts the following technical scheme: A method for preparing nitrogen-doped mesoporous carbon nanoalloy catalysts using dual-ligand MOFs, comprising the following steps:
[0008] S1, dissolving the soluble metal salt M1 in an organic solvent, and then adding tetrakis(4-methoxycarbonylphenyl)porphyrin, i.e. T(4-COOCH3)PP and trimesic acid, i.e. BTC, in a molar ratio of 1:(0.1-10) to obtain a mixed solution, stirring until the materials are completely dissolved, adjusting the pH value of the solution to 2-4, transferring the mixed solution into a polytetrafluoroethylene reactor, and reacting at 50-140°C for 2-48h, cooling to room temperature, separating and obtaining a precipitate, and drying to obtain a MOFs material with T(4-COOCH3)PP and BTC as dual ligands, referred to as M1-TCOPP-BTC-MOFs;
[0009] S2, dissolving the soluble metal salt M2 in an ethanol solution, adding the M1-TCOPP-BTC-MOFs prepared in step S1, wherein the molar ratio of the metal in the M1-TCOPP-BTC-MOFs to the metal in the soluble metal salt M2 is 10:1-1:10, stirring and mixing at room temperature, and vacuum drying to obtain a solid catalyst precursor M1-M2-TCOPP-BTC-MOFs;
[0010] S3. Take M1-M2-TCOPP-BTC-MOFs and grind them evenly, place them in a tubular furnace, anneal them at a temperature of 200-800° C. for 2-8 hours in an atmosphere of air, hydrogen or inert gas, cool them to room temperature and grind them to obtain a nitrogen-doped mesoporous carbon nanoalloy catalyst, namely M1-M2-NPC.
[0011] Further improvement of the method for preparing nitrogen-doped mesoporous carbon nanoalloy catalysts as dual-ligand MOFs:
[0012] Preferably, the molar ratio of porphyrin (T(4-COOCH3)PP) to trimesic acid (BTC) in step S1 is 1:(1-3).
[0013] Preferably, the soluble metal salt M1 is a single metal salt formed by one of Cu, Co, Ni, Zn, Al, Mn and Pd.
[0014] Preferably, the soluble metal salt M2 is a single metal salt formed by one of Cu, Co, Ni, Zn, Al, Mn, and Pd, or a composite metal salt formed by two or more of them, or a combination of any two or more of the single metal salts and the composite metal salts.
[0015] Preferably, the organic solvent is one or a combination of two or more of N,N-dimethylformamide (DMF), N,N-diethylformamide (DEF), acetonitrile, dimethyl sulfoxide, and triethanolamine.
[0016] Preferably, the organic solvent is a mixed solution of DMF and DEF, with a volume ratio of DMF to DEF of 1:1-1:10, preferably a volume ratio of 1:7.
[0017] Preferably, the inert gas in step S3 is one or a combination of two or more of nitrogen, argon, carbon dioxide and helium.
[0018] Preferably, in step S1, the pH value of the solution is adjusted with hydrochloric acid solution, nitric acid solution or sulfuric acid solution; the concentration of the sulfuric acid solution is 1-10 mol / L, preferably 3.3 mol / L.
[0019] Preferably, in step S1, the reaction temperature of the mixed solution in the polytetrafluoroethylene reactor is 120-140° C., and the reaction time is 20-24 h.
[0020] Preferably, in step S3, the annealing temperature is 400-500° C., and the annealing time is 2.5-4 h.
[0021] The second object of the present invention is to provide a use of a nitrogen-doped mesoporous carbon nanoalloy catalyst prepared by any of the above preparation methods in catalyzing furfural aqueous phase hydrogenation to prepare cyclopentanone.
[0022] Further improvements in the use of nitrogen-doped mesoporous carbon nanoalloy catalysts:
[0023] Preferably, the catalyst M1-M2-NPC and the furfural solution are mixed and added to a high-pressure reactor, the air in the high-pressure reactor is replaced with N2 and H2 in turn, the reactor is sealed, and H2 is introduced until the pressure reaches 1-20 MPa, stirring is started, and the reactor is heated to 80-200°C for reaction for 0.5-8h.
[0024] Preferably, the ratio of the mass of the added catalyst to the mass of furfural in the furfural solution is (10-30):100, and the preferred ratio is (15-20):100.
[0025] Preferably, hydrogen is introduced until the pressure reaches 1.5-3 MPa.
[0026] Preferably, the reaction kettle is heated to 140-180° C. for 4-6 hours.
[0027] Preferably, the solvent of the furfural solution is one or both of water and methanol, and the mass concentration of the furfural solution is 1%-30%.
[0028] Preferably, after the reaction is completed, the contents of furfural, furfuryl alcohol and cyclopentanone in the reaction mixture are analyzed by gas chromatograph internal standard method, the furfural conversion rate and cyclopentanone yield are calculated, and the recovered M1-M2-NPC catalyst can be directly or recycled after washing.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1) The present invention provides a method for preparing nitrogen-doped mesoporous carbon nanoalloy catalysts using dual-ligand MOFs. Tetrakis(4-methoxycarbonylphenyl)porphyrin and trimesic acid are designed as dual ligands, and bimetallic MOFs are prepared as precursors. The precursors are then annealed to prepare M1-M2-NPC carbon-based catalysts. The catalysts can be used to catalyze the conversion of furfural into cyclopentanone, thereby developing a new green production technology for cyclopentanone.
[0031] The preparation method uses trimesic acid and tetrakis(4-methoxycarbonylphenyl)porphyrin as dual ligands to prepare bimetallic MOFs as precursors, which can provide abundant metal active sites for coordination with metal ions. The prepared solid catalyst precursor has a hierarchical porous structure. The M1-M2-NPC obtained by annealing has a high specific surface area and a good pore structure, which is beneficial to the mass transfer process in the catalytic reaction and improves the catalyst activity. The trimesic acid and tetrakis(4-methoxycarbonylphenyl)porphyrin dual ligands form M1-M2-TCOPP-BTC-MOFs, and the metal atoms are more evenly distributed through coordination. Under pyrolysis conditions, the highly dispersed M1 and M2 metals are in situ converted into their metal nanoparticles, so that the obtained M1-M2-NPC catalyst has many active sites and is evenly dispersed, and has good stability.
[0032] By changing the ratio of the two ligands, tetrakis(4-methoxycarbonylphenyl)porphyrin and trimesic acid, the N content in M1-M2-NPC can be easily regulated, and the acidity, alkalinity, site and balance of the catalyst carrier can be controlled. In the process of catalyzing the conversion of furfural into cyclopentanone, the self-polymerization of furfural and the condensation of the intermediate furfuryl alcohol at high temperature in the aqueous phase system can be effectively prevented, thereby improving the conversion rate and selectivity of the catalytic reaction.
[0033] 2) The M1-M2@NPC catalyst prepared by the present invention is used to catalyze the conversion of furfural into cyclopentanone. The reaction process is as follows: the catalyst can be recycled multiple times, the catalytic efficiency is not significantly reduced, the cycle performance is good, and it meets the needs of industrial production. The catalyst is safe, non-toxic, green and efficient, environmentally friendly and harmless to the human body, meets the requirements of industrial green production, and has good application prospects.
[0034] DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0036] In the examples, furfural conversion and cyclopentanone selectivity are defined as:
[0037] Furfural conversion rate = (initial furfural amount – residual furfural amount after reaction) / initial furfural amount × 100%,
[0038] Cyclopentanone selectivity = amount of furfural converted into cyclopentanone / furfural consumed in the reaction × 100%.
[0039] Example 1
[0040] This embodiment provides a method for preparing Cu-Co-NPC catalyst 1, and is applied to catalyze furfural to prepare cyclopentanone, as follows:
[0041] S1. Preparation of Cu-Co-NPC catalyst 1:
[0042] Weigh 1.0473g Cu(NO3)2·6H2O and dissolve it in 80mL of organic solvent, wherein the organic solvent is a mixed solvent of DMF and DEF in a volume ratio of 1:7, then add 0.5012g of tetrakis(4-methoxycarbonylphenyl)porphyrin (i.e., T(4-COOCH3)PP) and 0.1243g of trimesic acid (i.e., BTC), wherein the molar ratio of T(4-COOCH3)PP and BTC is 1:1, stir until Cu(NO3)2·6H2O and other materials are completely dissolved, and adjust the solution to pH=3 with 3.3mol / L sulfuric acid solution. The mixed solution was then transferred into a polytetrafluoroethylene liner, sealed in a stainless steel autoclave, and reacted at 120°C for 24 hours. After cooling to room temperature, the reaction mixed solution was separated to obtain a precipitate, which was dried at 60°C overnight to obtain 0.6543 g of MOFs material with porphyrin (T(4-COOCH3)PP) and trimesic acid (BTC) as dual ligands, referred to as Cu-TCOPP-BTC-MOFs.
[0043] 0.1054 g of Co(NO3)2·6H2O was weighed and dissolved in 20 mL of ethanol solution, and 0.1054 g of the above Cu-TCOPP-BTC-MOFs was added, the molar ratio of the metal Cu in the added Cu-TCOPP-BTC-MOFs to the metal Co in Co(NO3)2·6H2O was 1:4, and the mixture was stirred at room temperature for 16 h. The mixed solution was vacuum dried at 80 °C to obtain a solid catalyst precursor Cu-Co-TCOPP-BTC-MOFs;
[0044] The solid catalyst precursor Cu-Co-TCOPP-BTC-MOFs was crushed evenly, placed in a quartz crucible and then placed in a tubular furnace. It was annealed at 500°C for 3 hours in an atmosphere with a nitrogen to hydrogen flow ratio of 2:1. After cooling to room temperature, it was ground and collected to obtain 0.1028 g of nitrogen-doped mesoporous carbon nanoalloy catalyst, namely Cu-Co-NPC catalyst 1.
[0045] S2, catalyzing furfural to prepare cyclopentanone:
[0046] A total of 20 mg of Cu-Co-NPC catalyst 1 was prepared according to the above method. 0.1 g of furfural was added to 5 mL of deionized water (the mass concentration of the furfural solution was 2%), and then added to the autoclave respectively. The mass of the added catalyst accounted for 20% of the mass of furfural in the furfural solution. The air in the autoclave was replaced with N2 and H2 in turn. The autoclave was sealed, and H2 was introduced until the pressure reached 3.0 MPa. The stirring of the autoclave was started, and the autoclave was heated to 180°C for 4 hours.
[0047] After the reaction is completed, the reaction mixture is cooled to room temperature, 10 mL of anhydrous ethanol is added, and the mixture is evenly mixed and then centrifuged and filtered to separate and recover the catalyst, which can be directly recycled.
[0048] The obtained filtrate was detected by gas chromatography internal standard method with cyclohexanone as internal standard, and the furfural conversion rate was calculated to be 99.9% and the cyclopentanone selectivity was 72%.
[0049] Embodiment 2:
[0050] This embodiment provides a method for preparing Cu-Co-NPC catalyst 2, and is applied to catalyze furfural to prepare cyclopentanone, as follows:
[0051] S1. Preparation of Cu-Co-NPC catalyst 2:
[0052] Weigh 1.0324 g of Cu(NO3)2·6H2O and dissolve it in 80 mL of an organic solvent, wherein the organic solvent is a mixed solvent of DMF and DEF in a volume ratio of 1:7. Then add 0.5012 g of tetrakis(4-methoxycarbonylphenyl)porphyrin (i.e., T(4-COOCH3)PP) and 0.2486 g of trimesic acid (i.e., BTC), wherein the molar ratio of T(4-COOCH3)PP to BTC is 1:2. Stir to completely dissolve the Cu(NO3)2·6H2O and other materials, and adjust the solution to pH=3 with 3.3 mol / L sulfuric acid solution. The mixed solution was then transferred into a polytetrafluoroethylene liner and sealed in a stainless steel autoclave. The reaction was continued at 120°C for 24 hours. After cooling to room temperature, the reaction mixed solution was separated to obtain a precipitate. The precipitate was dried at 60°C overnight to obtain 0.5756 g of MOFs material with porphyrin (T(4-COOCH3)PP) and trimesic acid (BTC) as dual ligands, referred to as Cu-TCOPP-BTC-MOFs.
[0053] Weigh 0.2012 g of Co(NO3)2·6H2O and dissolve it in 20 mL of ethanol solution, add 0.1076 g of the above-mentioned Cu-TCOPP-BTC-MOFs, the molar ratio of the metal Cu in the added Cu-TCOPP-BTC-MOFs to the metal Co in Co(NO3)2·6H2O is 1:4, stir at room temperature for 16 h, and dry the mixed solution in vacuum at 80 °C to obtain a solid catalyst precursor Cu-Co-TCOPP-BTC-MOFs.
[0054] The solid catalyst precursor Cu-Co-TCOPP-BTC-MOFs was crushed evenly, placed in a quartz crucible and then placed in a tubular furnace. It was annealed at 500°C for 3 hours in an atmosphere with a nitrogen to hydrogen flow ratio of 2:1. After cooling to room temperature, it was ground and collected to obtain 0.1423 g of nitrogen-doped mesoporous carbon nanoalloy catalyst, namely Cu-Co-NPC catalyst 2.
[0055] S2, catalyzing furfural to prepare cyclopentanone:
[0056] A total of 20 mg of Cu-Co-NPC catalyst 2 was prepared according to the above method. 0.1 g of furfural was added to 5 mL of deionized water (the mass concentration of the furfural solution was 2%), and then added to the autoclave respectively. The mass of the added catalyst accounted for 20% of the mass of furfural in the furfural solution. The air in the autoclave was replaced with N2 and H2 in turn. The autoclave was sealed, and H2 was introduced until the pressure reached 3.0 MPa. The stirring of the autoclave was started, and the autoclave was heated to 180°C for 4 hours.
[0057] After the reaction is completed, the reaction mixture is cooled to room temperature, 10 mL of anhydrous ethanol is added, and the mixture is evenly mixed and then centrifuged and filtered to separate and recover the catalyst, which can be directly recycled.
[0058] Compared with Example 1, due to the increase of the second ligand, the metal content in M1 after the reaction increases, and the amount of M2 added is adjusted to make the ratio of the two metals the same as in Example 1. In this embodiment, the nitrogen content in the catalyst is reduced by adjusting the molar ratio of the two ligands in the catalyst to reach a more suitable nitrogen content range, thereby improving the selectivity of cyclopentanone. The obtained filtrate is detected by gas chromatography internal standard method with cyclohexanone as the internal standard, and the furfural conversion rate is calculated to be 99.9%, and the cyclopentanone selectivity is 86%.
[0059] Embodiment 3:
[0060] This embodiment provides a method for applying a Cu-Co-NPC catalyst 2 to catalyze furfural to prepare cyclopentanone, which is as follows:
[0061] S1. Preparation of Cu-Co-NPC catalyst 2: refer to the specific steps in Example 2.
[0062] S2, catalyzing furfural to prepare cyclopentanone:
[0063] A total of 10 mg of Cu-Co-NPC catalyst 2 was prepared according to the above method. 0.1 g of furfural was added to 5 mL of deionized water (the mass concentration of the furfural solution was 2%), and then added to the autoclave respectively. The mass of the added catalyst accounted for 10% of the mass of furfural in the furfural solution. The air in the autoclave was replaced with N2 and H2 in turn. The autoclave was sealed, and H2 was introduced until the pressure reached 3.0 MPa. The stirring of the autoclave was started, and the autoclave was heated to 180°C for 4 hours.
[0064] Compared with Example 2, the ratio of the mass of the added catalyst to the mass of furfural in the furfural solution is adjusted in this example. The obtained filtrate is detected by gas chromatography internal standard method with cyclohexanone as the internal standard, and the furfural conversion rate is calculated to be 70%, and the cyclopentanone selectivity is 68%.
[0065] Embodiment 4:
[0066] This embodiment provides a method for applying a Cu-Co-NPC catalyst 2 to catalyze furfural to prepare cyclopentanone, which is as follows:
[0067] S1. Preparation of Cu-Co-NPC catalyst 2: refer to the specific steps in Example 2.
[0068] S2, catalyzing furfural to prepare cyclopentanone:
[0069] A total of 30 mg of Cu-Co-NPC catalyst 2 was prepared according to the above method. 0.1 g of furfural was added to 5 mL of deionized water (the mass concentration of the furfural solution was 2%), and then added to the autoclave respectively. The mass of the added catalyst accounted for 30% of the mass of furfural in the furfural solution. The air in the autoclave was replaced with N2 and H2 in turn. The autoclave was sealed, and H2 was introduced until the pressure reached 3.0 MPa. The stirring of the autoclave was started, and the autoclave was heated to 180°C for 4 hours.
[0070] Compared with Example 2, the ratio of the mass of the added catalyst to the mass of furfural in the furfural solution is adjusted in this example. The obtained filtrate is detected by gas chromatography internal standard method with cyclohexanone as internal standard, and the furfural conversion rate is calculated to be 99.9%, and the cyclopentanone selectivity is 84%.
[0071] Embodiment 5:
[0072] This embodiment provides a method for preparing a Cu-Ni-NPC catalyst, and is applied to catalyze furfural to prepare cyclopentanone, as follows:
[0073] S1. Preparation of Cu-Ni-NPC catalyst:
[0074] Weigh 1.0324 g of Cu(NO3)2·6H2O and dissolve it in 80 mL of an organic solvent, wherein the organic solvent is a mixed solvent of DMF and DEF in a volume ratio of 1:7. Then add 0.5012 g of tetrakis(4-methoxycarbonylphenyl)porphyrin (i.e., T(4-COOCH3)PP) and 0.2486 g of trimesic acid (i.e., BTC), wherein the molar ratio of T(4-COOCH3)PP to BTC is 1:2. Stir to completely dissolve the Cu(NO3)2·6H2O and other materials, and adjust the solution to pH=3 with 3.3 mol / L sulfuric acid solution. The mixed solution was then transferred into a polytetrafluoroethylene liner and sealed in a stainless steel autoclave. The reaction was continued at 120°C for 24 hours. After cooling to room temperature, the reaction mixed solution was separated to obtain a precipitate. The precipitate was dried at 60°C overnight to obtain 0.5756 g of MOFs material with porphyrin (T(4-COOCH3)PP) and trimesic acid (BTC) as dual ligands, referred to as Cu-TCOPP-BTC-MOFs.
[0075] Weigh 0.1011 g of Ni(NO3)2·6H2O and dissolve it in 20 mL of ethanol solution, add 0.1076 g of the above-mentioned Cu-TCOPP-BTC-MOFs, the molar ratio of the metal Cu in the added Cu-TCOPP-BTC-MOFs to the metal Ni in Ni(NO3)2·6H2O is 1:2, stir at room temperature for 16 h, and dry the mixed solution in vacuum at 80 °C to obtain a solid catalyst precursor Cu-Ni-TCOPP-BTC-MOFs.
[0076] The solid catalyst precursor Cu-Ni-TCOPP-BTC-MOFs was crushed evenly, placed in a quartz crucible and then placed in a tubular furnace. It was annealed at 500°C for 3 hours in an atmosphere with a nitrogen to hydrogen flow ratio of 2:1. After cooling to room temperature, it was ground and collected to obtain 0.1002 g of nitrogen-doped mesoporous carbon nanoalloy catalyst, namely Cu-Ni-NPC catalyst.
[0077] S2, catalyzing furfural to prepare cyclopentanone:
[0078] A total of 20 mg of Cu-Ni-NPC catalyst was prepared according to the above method. 0.1 g of furfural was added to 5 mL of deionized water (the mass concentration of the furfural solution was 2%), and then added to the autoclave respectively. The mass of the added catalyst accounted for 20% of the mass of furfural in the furfural solution. The air in the autoclave was replaced with N2 in turn, the autoclave was sealed, and H2 was introduced until the pressure reached 3.0 MPa. The stirring of the autoclave was started, and the autoclave was heated to 180°C for 4 hours.
[0079] After the reaction is completed, the reaction mixture is cooled to room temperature, 10 mL of anhydrous ethanol is added, and the mixture is evenly mixed and then centrifuged and filtered to separate and recover the catalyst, which can be directly recycled.
[0080] The obtained filtrate was detected by gas chromatography internal standard method with cyclohexanone as internal standard, and the furfural conversion rate was calculated to be 99.9% and the cyclopentanone selectivity was 80%.
[0081] Embodiment 6:
[0082] This embodiment provides a method for preparing a Co-Ni-NPC catalyst, and is applied to catalyze furfural to prepare cyclopentanone, as follows:
[0083] S1. Preparation of Co-Ni-NPC catalyst:
[0084] Weigh 1.0241 g of Co(NO3)2·6H2O and dissolve it in 80 mL of an organic solvent, wherein the organic solvent is a mixed solvent of DMF and DEF in a volume ratio of 1:7. Then add 0.5012 g of tetrakis(4-methoxycarbonylphenyl)porphyrin (i.e., T(4-COOCH3)PP) and 0.2486 g of trimesic acid (i.e., BTC), wherein the molar ratio of T(4-COOCH3)PP to BTC is 1:2. Stir to completely dissolve the Co(NO3)2·6H2O and other materials, and adjust the solution to pH=3 with 3.3 mol / L sulfuric acid solution. The mixed solution was then transferred into a polytetrafluoroethylene liner and sealed in a stainless steel autoclave. The reaction was continued at 120°C for 24 hours. After cooling to room temperature, the reaction mixed solution was separated to obtain a precipitate. The precipitate was dried at 60°C overnight to obtain 0.4687 g of MOFs material with porphyrin (T(4-COOCH3)PP) and trimesic acid (BTC) as dual ligands, referred to as Co-TCOPP-BTC-MOFs.
[0085] Weigh 0.1123 g of Ni(NO3)2·6H2O and dissolve it in 20 mL of ethanol solution, add 0.1025 g of the above-mentioned Co-TCOPP-BTC-MOFs, the molar ratio of the metal Cu in the added Cu-TCOPP-BTC-MOFs to the metal Co in Co(NO3)2·6H2O is 1:2, stir at room temperature for 16 h, and dry the mixed solution in vacuum at 80 °C to obtain the solid catalyst precursor Co-Ni-TCOPP-BTC-MOFs.
[0086] The solid catalyst precursor Co-Ni-TCOPP-BTC-MOFs was crushed evenly, placed in a quartz crucible and then placed in a tubular furnace. It was annealed at 500°C for 3 hours in an atmosphere with a nitrogen to hydrogen flow ratio of 2:1. After cooling to room temperature, it was ground and collected to obtain 0.1002 g of nitrogen-doped mesoporous carbon nanoalloy catalyst, namely Co-Ni-NPC catalyst 2.
[0087] S2, catalyzing furfural to prepare cyclopentanone:
[0088] A total of 20 mg of Co-Ni-NPC catalyst was prepared according to the above method. 0.1 g of furfural was added to 5 mL of deionized water (the mass concentration of the furfural solution was 2%), and then added to the autoclave respectively. The mass of the added catalyst accounted for 20% of the mass of furfural in the furfural solution. The air in the autoclave was replaced with N2 and H2 in turn. The autoclave was sealed, and H2 was introduced until the pressure reached 3.0 MPa. The stirring of the autoclave was started, and the autoclave was heated to 180°C for 4 hours.
[0089] After the reaction is completed, the reaction mixture is cooled to room temperature, 10 mL of anhydrous ethanol is added, and the mixture is evenly mixed and then centrifuged and filtered to separate and recover the catalyst, which can be directly recycled.
[0090] The obtained filtrate was detected by gas chromatography internal standard method with cyclohexanone as internal standard, and the furfural conversion rate was calculated to be 99.9% and the cyclopentanone selectivity was 83%.
[0091] Embodiment 7:
[0092] This embodiment provides a method for applying a Cu-Co-NPC catalyst 2 to catalyze furfural to prepare cyclopentanone, which is as follows:
[0093] S1. Preparation of Cu-Co-NPC catalyst 2: refer to the specific steps in Example 2.
[0094] S2, catalyzing furfural to prepare cyclopentanone:
[0095] A total of 50 mg of Cu-Co-NPC catalyst 2 was prepared according to the above method. 0.25 g of furfural was added to 5 mL of deionized water (the mass concentration of the furfural solution was 5%), and then added to the autoclave respectively. The mass of the added catalyst accounted for 20% of the mass of furfural in the furfural solution. The air in the autoclave was replaced with N2 and H2 in turn. The autoclave was sealed, and H2 was introduced until the pressure reached 3.0 MPa. The stirring of the autoclave was started, and the autoclave was heated to 180°C for 4 hours.
[0096] After the reaction is completed, the reaction mixture is cooled to room temperature, 10 mL of anhydrous ethanol is added, and the mixture is evenly mixed and then centrifuged and filtered to separate and recover the catalyst, which can be directly recycled.
[0097] Compared with Example 2, the present embodiment increases the concentration of the reactant furfural in the preparation of cyclopentanone by catalyzing furfural, and the polycondensation side reaction is obvious during the reaction, resulting in a decrease in the furfural conversion rate and the selectivity of cyclopentanone. The obtained filtrate is detected by gas chromatography internal standard method with cyclohexanone as the internal standard, and the calculated furfural conversion rate is 90%, and the cyclopentanone selectivity is 40%.
[0098] Embodiment 8:
[0099] This embodiment provides a method for applying a Cu-Co-NPC catalyst 2 to catalyze furfural to prepare cyclopentanone, which is as follows:
[0100] S1. Preparation of Cu-Co-NPC catalyst 2: refer to the specific steps in Example 2.
[0101] S2, catalyzing furfural to prepare cyclopentanone:
[0102] A total of 50 mg of Cu-Co-NPC catalyst 2 was prepared according to the above method. 0.50 g of furfural was added to 5 mL of deionized water (the mass concentration of the furfural solution was 10%) and then added to the autoclave respectively. The mass of the added catalyst accounted for 20% of the mass of furfural in the furfural solution. The air in the autoclave was replaced with N2 and H2 in turn. The autoclave was sealed, and H2 was introduced until the pressure reached 3.0 MPa. The stirring of the autoclave was started, and the autoclave was heated to 180°C for 4 hours.
[0103] Compared with Examples 2 and 5, after the furfural concentration of the reactant is further increased in this embodiment, the polycondensation side reaction is obvious in the reaction process, resulting in a decrease in the furfural conversion rate and the selectivity of cyclopentanone. The obtained filtrate is detected by gas chromatography internal standard method with cyclohexanone as the internal standard, and the calculated furfural conversion rate is 65%, and the cyclopentanone selectivity is 16%.
[0104] Embodiment 9:
[0105] This embodiment provides a method for preparing a Cu-Co-Ni-NPC catalyst, and is applied to catalyze furfural to prepare cyclopentanone, as follows:
[0106] S1. Preparation of Cu-Co-Ni-NPC catalyst:
[0107] Weigh 1.0324 g of Cu(NO3)2·6H2O and dissolve it in 80 mL of an organic solvent, wherein the organic solvent is a mixed solvent of DMF and DEF in a volume ratio of 1:7. Then add 0.5012 g of tetrakis(4-methoxycarbonylphenyl)porphyrin (i.e., T(4-COOCH3)PP) and 0.2486 g of trimesic acid (i.e., BTC), wherein the molar ratio of T(4-COOCH3)PP to BTC is 1:2. Stir to completely dissolve the Cu(NO3)2·6H2O and other materials, and adjust the solution to pH=3 with 3.3 mol / L sulfuric acid solution. The mixed solution was then transferred into a polytetrafluoroethylene liner and sealed in a stainless steel autoclave. The reaction was continued at 120°C for 24 hours. After cooling to room temperature, the reaction mixed solution was separated to obtain a precipitate. The precipitate was dried at 60°C overnight to obtain 0.5756 g of MOFs material with porphyrin (T(4-COOCH3)PP) and trimesic acid (BTC) as dual ligands, referred to as Cu-TCOPP-BTC-MOFs.
[0108] Weigh 0.2012 g of Co(NO3)2·6H2O and 0.2012 g of Ni(NO3)2·6H2O and dissolve them in 20 mL of ethanol solution, add 0.1076 g of the above-mentioned Cu-TCOPP-BTC-MOFs, stir at room temperature for 16 h, and dry the mixed solution in vacuum at 80 °C to obtain a solid catalyst precursor Cu-Co-Ni-TCOPP-BTC-MOFs.
[0109] The solid catalyst precursor Cu-Co-Ni-TCOPP-BTC-MOFs was crushed evenly, placed in a quartz crucible and then placed in a tubular furnace. It was annealed at 500°C for 3 hours in an atmosphere with a nitrogen to hydrogen flow ratio of 2:1. After cooling to room temperature, it was ground and collected to obtain 0.1924 g of nitrogen-doped mesoporous carbon nanoalloy catalyst, namely Cu-Co-Ni-NPC catalyst.
[0110] S2, catalyzing furfural to prepare cyclopentanone:
[0111] A total of 20 mg of Cu-Co-Ni-NPC catalyst was prepared according to the above method, added to 5 mL of deionized water (the mass concentration of furfural solution was 2%), and then added to the autoclave respectively. The mass of the added catalyst accounted for 20% of the mass of furfural in the furfural solution. The air in the autoclave was replaced with N2 and H2 in turn. The autoclave was sealed, and H2 was introduced until the pressure reached 3.0 MPa. The stirring of the autoclave was started, and the autoclave was heated to 180°C for 4 hours.
[0112] After the reaction is completed, the reaction mixture is cooled to room temperature, 10 mL of anhydrous ethanol is added, and the mixture is evenly mixed and then centrifuged and filtered to separate and recover the catalyst, which can be directly recycled.
[0113] Compared with Example 2, the soluble metal salt M2 in this example uses a combination of two single metal salts to prepare a three-component nano alloy catalyst. The obtained filtrate uses cyclohexanone as an internal standard, and the furfural conversion rate is calculated to be 99.9% and the cyclopentanone selectivity is 80% by gas chromatography internal standard method detection.
[0114] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. Application of a dual-ligand MOFs-based nitrogen-doped mesoporous carbon nanoalloy catalyst in catalyzing furfural aqueous phase hydrogenation to produce cyclopentanone, characterized in that: The method for preparing nitrogen-doped mesoporous carbon nanoalloy catalysts using dual-ligand MOFs comprises the following steps: S1, dissolving the soluble metal salt M1 in an organic solvent, and then adding tetrakis(4-methoxycarbonylphenyl)porphyrin and trimesic acid in a molar ratio of 1:2 to obtain a mixed solution, stirring until the materials are completely dissolved, adjusting the pH value of the solution to 2-4, transferring the mixed solution into a polytetrafluoroethylene reactor, and continuously reacting at a temperature of 50-140°C for 2-48h, cooling to room temperature, separating and obtaining a precipitate, and drying to obtain a MOFs material with T(4-COOCH3)PP and BTC as dual ligands, referred to as M1-TCOPP-BTC-MOFs; S2, dissolving the soluble metal salt M2 in an ethanol solution, adding the M1-TCOPP-BTC-MOFs prepared in step S1, wherein the molar ratio of the metal in the M1-TCOPP-BTC-MOFs to the metal in the soluble metal salt M2 is 1:(2-4), stirring and mixing at room temperature, and vacuum drying to obtain a solid catalyst precursor M1-M2-TCOPP-BTC-MOFs; S3, taking M1-M2-TCOPP-BTC-MOFs and crushing them evenly, placing them in a tube furnace, annealing them at a temperature of 200-800°C for 2-8h in a hydrogen and inert gas atmosphere, cooling them to room temperature and grinding them to obtain nitrogen-doped mesoporous carbon nanoalloy catalyst M1-M2-NPC; wherein M1 and M2 are different metals; The specific application method is as follows: the catalyst M1-M2-NPC and the furfural solution are mixed and added to a high-pressure reactor, the air in the high-pressure reactor is replaced with N2 and H2 in turn, the reactor is sealed, and H2 is introduced until the pressure reaches 3Mpa, stirring is started, and the reactor is heated to 180°C for 4 hours; the ratio of the mass of the added catalyst to the mass of furfural in the furfural solution is (20-30):100; the mass concentration of the furfural solution is 2%.
2. The use according to claim 1, characterized in that: The soluble metal salt M1 is a single metal salt formed by one of Cu, Co, Ni, Zn, Al, Mn and Pd.
3. The use according to claim 1, characterized in that: The soluble metal salt M2 is a single metal salt formed by one of Cu, Co, Ni, Zn, Al, Mn, and Pd, or a composite metal salt formed by two or more of them.
4. The use according to claim 1, characterized in that: The organic solvent is one or a combination of two or more of N,N-dimethylformamide, N,N-diethylformamide, acetonitrile, dimethyl sulfoxide and triethanolamine.
5. The use according to claim 1, characterized in that: The solvent of the furfural solution is one or both of water and methanol.
6. The use according to claim 1, characterized in that: After the reaction is completed, the contents of furfural, furfuryl alcohol and cyclopentanone in the reaction mixture are analyzed by gas chromatography internal standard method, and the furfural conversion rate and cyclopentanone yield are calculated. The recovered M1-M2-NPC catalyst can be directly or recycled after washing.
Citation Information
Patent Citations
Nitrogen-doped mesoporous carbon supported alloy nano-catalyst and application thereof
CN114849755A